Phenomenological critique of representative democracy - Pereira, Paula Cristina (Opción, 2016)
Considering that representative democracy has today ensured stratification at several levels, bolstered by economy as an ideology which maintains the dominating and the dominated in their rightful place, this paper intends to highlight a number of totalitarian tendencies, from a phenomenological perspective, that have revealed the limits and challenges of the power mechanisms of representative democracy. Contending that democracy is experienced and not simply a regime, we have highlighted the need for a critical attitude that deconstructs totalitarian discourses or narratives.